Relation of synovitis to knee pain using contrast-enhanced MRIs. Issue 10 (14th May 2010) - Baker, K; Grainger, A; Niu, J; Clancy, M; Guermazi, A; Crema, M; Hughes, L; Buckwalter, J; Wooley, A; Nevitt, M; Felson, D T
Abstract : Background: It has been suggested that synovitis causes joint pain. On non-contrast-enhanced MRIs synovial thickening cannot be assessed and on these images synovitis has been inconsistently associated with pain. Objective: To assess synovial thickening in relation to knee pain severity among subjects in the Multicenter Osteoarthritis Study (MOST) using contrast-enhanced (CE) MRI. Methods: MOST is a cohort study of people who have, or are at high risk of, knee osteoarthritis (OA). An unselected subset of 535 participants who volunteered underwent CE 1.5 T MRI of one knee. Synovitis was scored in six compartments and a summary score was created. Knee pain severity was assessed using the maximum item score on the Western Ontario and McMaster Osteoarthritis Index (WOMAC) pain scale. The association between synovitis and pain severity was examined using a logistic regression model adjusting for age, sex, body mass index (BMI), MRI bone marrow lesions and effusions in the whole sample and in a subgroup without radiographic OA. Results: 454 of the 535 subjects undergoing CE MRI had complete data on synovitis and WOMAC pain. Mean age was 59 years, mean BMI 30 and 48% were women. In knees with moderate pain, 80% had synovitis. For knee pain, synovitis conferred a 9.2-fold increased odds compared with those without synovitis. In knees without radiographic OA (n=329), there was also an association of synovitis with an increased prevalence of pain. Conclusion: Synovitis has a strong relation with knee pain severity, an association detected more clearly with CE MRI than suggested by previous studies using non-CE MRI measures of synovitis.